Strengthening Students' Self-Control Through Islamic Religious Education Learning In Preventing Bullying - Hafidurrahman, Moh; Dannur, Moh; Fauzan (Al-Riwayah : Jurnal Kependidikan, 2023)
This research specifically examines the values ​​of mujahadah al-nafs or self-control in Islamic education materials as well as mujahadah al-nafs in preventing bullying behavior in the educational environment. By using a literature review, this research will examine articles from several national or international journals. Some of the findings in this research include: first, there are several values ​​in Islam that can be internalized in Islamic education learning which focuses on tazkiyatun al-nafs, purity of soul which will lead students to al-hikmah (wisdom). Second, mujahadah al-nafs does not only focus on the ability to self-control in the meaning of dhohir but more on purity of heart as the basis of all human activities. The third is tolerance, attitudes and behavior are very important in preventing bullying, and this can be the key to creating a safer and more inclusive environment at school. It is hoped that this research will become part of the school's reference in minimizing bullying behavior in educational institutions. Keywords (Self-control, Mujahada, bullying)